An evaluation of SERVQUAL and patient loyalty in an emerging country context - TARIM, MEHVEŞ (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2010)
The growth of the service sector in the US spawned a strong interest and growing body of literature related to the measurement of service quality. SERVQUAL, a multi-item scale first proposed by Parasuraman, Zeithaml, and Berry (1985), has been used for measuring customer perceptions of service quality across a wide variety of service environments including healthcare in the US. There is a dearth of research that relates to an evaluation of SERVQUAL across various cultural and economic environments. This empirical study is an attempt to fill this gap by focusing on the healthcare environment in Istanbul, Turkey. In addition to a rigorous evaluation of SERVQUAL using confirmatory factor analysis, measures of internal consistency and discriminant validity, the relationships between the various dimensions of SERVQUAL, an overall measure of service quality and patient loyalty are evaluated using structural equations modelling and path analysis. A number of hypotheses are developed and tested. The results suggest that SERVQUAL and its dimensions of perceived service quality are reliable and valid across cultural and economic environments in the context of healthcare/hospital albeit some need for adaptation. Path analysis indicates that service quality directly affects both overall quality of and feelings toward hospital services. Overall quality affects customer repatronage intentions and feelings towards hospital services. However, no significant relationship was found between service quality and repatronage intention.
Keywords: SERVQUAL; patient loyalty; healthcare; Turkey; SERVICE QUALITY; CUSTOMER SATISFACTION; CONSUMER PERCEPTIONS; MARKET SHARE; SCALE; PROFITABILITY; REASSESSMENT; EXPECTATIONS; PARADIGM; CULTURES